2023
DOI: 10.3389/fmicb.2022.1064095
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles enhance the efficacy of aminoglycosides against antibiotic-resistant bacteria

Abstract: As the threat of antimicrobial-resistant bacteria compromises the safety and efficacy of modern healthcare practices, the search for effective treatments is more urgent than ever. For centuries, silver (Ag) has been known to have antibacterial properties and, over the past two decades, Ag-based nanoparticles have gained traction as potential antimicrobials. The antibacterial efficacy of Ag varies with structure, size, and concentration. In the present study, we examined Ag nanoparticles (AgNPs) for their antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Another study reported that AgNPs were effective against CRAB and could inhibit biofilm formation, a major contributor to antibiotic resistance [ 69 ]. AgNPs have also been shown to enhance the activity of conventional antibiotics, making them more effective against antibiotic-resistant bacteria such as E. coli [ 89 ]. Despite the promising antimicrobial activity of AgNPs, the development and application of these nanoparticles as antimicrobial agents still face some challenges, such as the potential for toxicity to plants, animals, and human cells; for this reason, a comprehensive toxicological evaluation is necessary [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that AgNPs were effective against CRAB and could inhibit biofilm formation, a major contributor to antibiotic resistance [ 69 ]. AgNPs have also been shown to enhance the activity of conventional antibiotics, making them more effective against antibiotic-resistant bacteria such as E. coli [ 89 ]. Despite the promising antimicrobial activity of AgNPs, the development and application of these nanoparticles as antimicrobial agents still face some challenges, such as the potential for toxicity to plants, animals, and human cells; for this reason, a comprehensive toxicological evaluation is necessary [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Separately, PVA, CD, and AgNPs at suitable concentrations are known to be non-toxic for different animal cells. [83][84][85] As an atypical macromolecule, HAG's cytocompatibility has never been examined before. Pure HAG at low to moderate concentrations was biocompatible and even promoted cell growth (Figure S7, Supporting Information).…”
Section: Cytocompatibility and Electrical Stimulation Of Fibroblast P...mentioning
confidence: 99%
“…Novel and unconventional methods for antimicrobial treatment are currently being explored for potential therapeutic applications. Some of the most promising approaches include bacteriophage therapy [12], repurposing existing drugs [13], antimicrobial peptides, small molecules, antibodies, natural compounds, anti-virulence agents, vaccines, immunomodulators, and employing silver nanoparticles (AgNPs) [14][15][16][17][18]. Amongst all the strategies stated previously, nanotechnology has shown good progress, and its influence has grown immensely in many sectors.…”
Section: Introductionmentioning
confidence: 99%
“…aerogenes [16,[33][34][35][36][37]. Although the precise mechanism remains unclear, studies suggest that AgNPs impact the bacterial cell membrane and interfere with ribosome and protein synthesis.…”
Section: Introductionmentioning
confidence: 99%